Leptogenopapus mirabilis, a new genus and species of Lomechusini (Coleoptera: Staphylinidae, Aleocharinae) from Papua New Guinea associated with ants of the genus Leptogenys Roger - Hlaváč, Peter; Janda, Milan (Zootaxa, 2009)
Leptogenopapus mirabilis, gen. n., sp. n. is described based on the single male collected from foraging colony of Leptogenys breviceps Viehmeyer in Papua New Guinea. The genus is a member of the tribe Lomechusini (Coleoptera: Staphylinidae, Aleocharinae) and is most closely related to Leptogenoxenus Kistner. The list of all Staphylinidae associated with the ant genus Leptogenys Roger is given.